Descriptive Study of Neonatal Death in Neonatal Care Unit of Baghdad Teaching Hospital / Medical city / Baghdad (2007-2009) - Numan N. Hameed; Baraa N. Abed (مجلة كلية الطب, 2012)
Background: In developing countries, neonatal death account for 99% of neonatal deaths in the world. In Iraq, the neonatal death rates are still unknown. Objectives: To assess the death rate and the major causes of neonatal death in the neonatal care unit (NCU) in Baghdad Teaching Hospital-Medical City/ Baghdad. Patients &Methods: A descriptive study of 564 neonatal deaths in the neonatal care unit (NCU) from 1st of January 2007 to 31st of December 2009 in Baghdad Teaching Hospital-Medical City/ Baghdad was carried out, and the causes of death as registered in the neonatal medical records and death certificates were studied. Results: Neonatal death rate relative to admission was (18.5%). The Neonatal death rates were lower in 2007(15%) than 2008(20%) and 2009(19.2%), of 564 total neonatal deaths, males were 329 (58.3%), 235 (41.7%) were females with male to female ratio was 1.4:1. Eighty percent of neonatal deaths were preterm deliveries and (79%) were low birth weight (< 2.5 kg). Major causes of death were: Respiratory problems (62.8%), followed by congenital anomalies (17%), neonatal infections (11.2%) and birth asphyxia (9%). Conclusions: The Neonatal death rate was lower in 2007 than 2008 and 2009. There was a high male to female ratio, and high percent of preterm deliveries and LBW. The main causes of death were respiratory problems, congenital anomalies and neonatal infections.